LAPAROSCOPY FOR THE RECOVERY OF REPRODUCTIVE HEALTH IN WOMEN WITH POLYCYSTIC OVARY SYNDROME - I. N. Medvedevа; A. B. Khuraseva; K. S. Svyatchenko; T. A. Biryukova (IRBIS LLC, 2018)
Aim: to analyze the usefulness of laparoscopic methods for the recovery of reproductive health in women with polycystic ovary syndrome (PCOS).Materials and methods. A continuous retrospective analysis of 56 outpatient cards and case histories of women with PCOS and concomitant infertility for the period from 2013 to 2015 was conducted using the documentation from the Kursk Regional Perinatal Center. The average age of the patients was 28.29 ± 4.43 years, the duration of infertility - from 1 to 15 years. Anamnestic and clinical data, concomitant pathology and long-term results of laparoscopic treatment and diagnostic procedures were studied.Results. The patients underwent surgical treatment after conservative therapy failed to restore their fertility. As a result, 49 women (87.5%) were able to restore the regular menstrual cycle and 35 women (62.5%) got pregnant.Conclusion. The use of laparoscopy revealed the ultimate cause of infertility and allowed for surgical treatment able to restore the reproductive women's health.